Great ape origins of personality maturation and sex differences a study of orangutans and chimpanzees. [article]. - Weiss, Alexander; King, James E.
Human personality development evinces increased emotional stability, prosocial tendencies, and responsibility. One hypothesis offered to explain this pattern is social-investment theory, which posits that culturally defined social roles, including marriage and employment, are responsible for the increased maturity. Alternatively, five-factor theory emphasizes the role of biological factors, such as those governing physical development, which may predate the emergence of humans. Five-factor theory, unlike social investment theory, predicts that all or some of the human personality developmental trends should be present in great apes, our closest evolutionary relatives. To test this prediction and to better understand the evolutionary origins of sex differences, we examined age and sex differences in the chimpanzees and orangutans personality domains extraversion, dominance, neuroticism, and agreeableness. We also examined the activity and gregariousness facets of extraversion and the orangutan intellect domain. Extraversion and neuroticism declined across age group in both species, in common with humans. A significant interaction indicated that agreeableness declined on orangutans but increased in chimpanzees, as it does in humans, though this may reflect differences in how agreeableness was defined in each species. Significant interactions indicated that male chimpanzees, unlike male orangutans, displayed higher neuroticism scores than females and maintained higher levels of activity and dominance into age than female chimpanzees, male orangutans, and female orangutans. Personality-age correlations were comparable across orangutan and chimpanzees and were similar to those reported in human studies. Sex differences were stronger in chimpanzees than in humans or orangutans. These findings support five-factor theory, suggest the role of gene-culture coevolution in shaping personality development, and suggest that sex differences evolved independently in different species. - - (from the authors)
Keywords: Personality-Periodicals.; Development-Periodicals.; Five-factor theory-Periodicals.; Social-investment theory-Periodicals.